Moni Iudeorum: an enigmatic early place-name for St David's. (1st December 2019) - Aitchison, Nick
Moni Iudeorum is recorded in Annales Cambriae as St David's place of death. The first element of this place-name may be identified with Middle Welsh Mynyw, modern St David's. Its second is obscure but has traditionally been interpreted as referring to the early Irish population group the Déisi, attesting early Irish settlement in south-west Wales. However, this interpretation rests only on a scribal emendation when others are equally, if not more, plausible. This paper reassesses the evidence, proposes a new, more minor, emendation, Moniu Deorum '*Moniu of the Gods', and examines this within a wider early Christian context.